(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
The article is devoted to a deep analysis of air pollution, its impact on human health and environmental consequences. The problem of air pollution on a global and Uzbek scale, its main sources (industry, motor transport, natural factors), health consequences (respiratory, cardiovascular diseases, oncological diseases) and solutions are studied. Modern monitoring systems and environmental strategies for improving air quality in industrial regions of Uzbekistan are proposed. The study is based on modern scientific literature, and also pays attention to the economic and social aspects of the problem.